Pathologies of the hearing aid under the influence of global climate change and ecology. Issue 2 (December 2021) - Ryzhkin, N; Ivanova, A; Savchenko, Y; Polin, R; Korobov, I
Abstract: This article discusses the pathological changes of the hearing aid in connection with the deterioration of the environmental situation around the world, presents the psychophysical features that deal with the struggle of children with hearing impairment (hard of hearing and deaf). The method of physical education in the course of classes in the wrestling section for the adaptation and harmonious physical development of hard-of-hearing children is proposed and investigated. In our opinion, exercises in wrestling contribute to the development of a number of many valuable physical and psychological qualities that are necessary for a child with hearing impairment. The hypothesis of the study is based on the assumption that the inclusion of special developed methods for wrestling will allow to achieve significant results in a short time in children with hearing impairment. The use of wrestling exercises allows you to maximize the development of the functions of these analyzers for deaf children to more effectively participate in the compensation of lost qualities as a result of impaired hearing aid.